Pembelajaran Materi Koordinat Kartesius melalui Model Pembelajaran Kooperatif Tipe TAI Berbantuan Videoscribe - Zahratul Suci; Suryawati Suryawati; Erni Maidiyah (Universitas Syiah Kuala, 2020)
Student learning activities can be improved by a Team Assisted Individualization (TAI) cooperative model using videoscribe. Video scribe learning media could increase students' interest in learning mathematics. This study aims to determine whether the implementation of the Team Assisted Individualization (TAI) type cooperative learning model using videoscribe increase student learning outcomes at a junior high school, SMP IT Lukmanul Hakim. Data on student learning outcomes was obtained from a posttest and analyzed quantitatively using a t-test. Hypothesis test of learning outcomes data using the t-test with a significant level (α) = 0.05 and degrees of freedom (dk) = 15 obtained tcount t table (7.74 1.75). This study concluded that the application of the Team Assisted Individualization (TAI) type cooperative model using videoscribe on Cartesian coordinates material has succecced and the students were engaged in the learning activities.